NECESSIDADES ALIMENTARES ESPECIAIS: O CUIDADO E A BUSCA DA EQUIDADE NA ATENÇÃO À SAÚDE - Luciana Maria Cerqueira Castro; Inês Rugani Ribeiro de Castro (Universidade do Estado do Rio de Janeiro, 2014)
Special dietary needs are a reality for significant portions of the population in Brazil. However, they remain invisible and / or ancillary in health programs. Developing and assuring qualified care for people with such needs should be seen as key elements to building equity in health care. Thus, we have had the honor to assemble this issue reserved to the topic "Assistance to special dietary needs in SUS (Unified Health System)," resulting from a partnership between DEMETRA Magazine and the General Coordination of Food and Nutrition (CGAN) of the Brazilian Ministry of Health. The purpose is to help overcome the shortage of publications and support managers and professionals on organizing and providing care in SUS for people who have some kind of special dietary needs. DOI: http://dx.doi.org/10.12957/demetra.2014.11953